Comparative effects of neurally adjusted ventilatory assist and variable pressure support on lung and diaphragmatic function in a model of acute respiratory distress syndrome: A randomised animal study. Issue 1 (January 2021) - Scharffenberg, Martin; Moraes, Lillian; Güldner, Andreas; Huhle, Robert; Braune, Anja; Zeidler-Rentzsch, Ines; Kasper, Michael; Kunert-Keil, Christiane; Koch, Thea; Pelosi, Paolo; Rocco, Patricia R.M.; Gama de Abreu, Marcelo; et al.
Abstract : BACKGROUND: Variable assisted mechanical ventilation has been shown to improve lung function and reduce lung injury. However, differences between extrinsic and intrinsic variability are unknown. OBJECTIVE: To investigate the effects of neurally adjusted ventilatory assist (NAVA, intrinsic variability), variable pressure support ventilation (Noisy PSV, extrinsic variability) and conventional pressure-controlled ventilation (PCV) on lung and diaphragmatic function and damage in experimental acute respiratory distress syndrome (ARDS). DESIGN: Randomised controlled animal study. SETTING: University Hospital Research Facility. SUBJECTS: A total of 24 juvenile female pigs. INTERVENTIONS: ARDS was induced by repetitive lung lavage and injurious ventilation. Animals were randomly assigned to 24 h of either: 1) NAVA, 2) Noisy PSV or 3) PCV ( n =8 per group). Mechanical ventilation settings followed the ARDS Network recommendations. MEASUREMENTS: The primary outcome was histological lung damage. Secondary outcomes were respiratory variables and patterns, subject-ventilator asynchrony (SVA), pulmonary and diaphragmatic biomarkers, as well as diaphragmatic muscle atrophy and myosin isotypes. RESULTS: Global alveolar damage did not differ between groups, but NAVA resulted in less interstitial oedema in dorsal lung regions than Noisy PSV. Gas exchange and SVA incidence did not differ between groups. Compared with Noisy PSV, NAVA generated higher coefficients of variation of tidal volume and respiratory rate. During NAVA, only 40.4% of breaths were triggered by the electrical diaphragm signal. The IL-8 concentration in lung tissue was lower after NAVA compared with PCV and Noisy PSV, whereas Noisy PSV yielded lower type III procollagen mRNA expression than NAVA and PCV. Diaphragmatic muscle fibre diameters were smaller after PCV compared with assisted modes, whereas expression of myosin isotypes did not differ between groups. CONCLUSION: Noisy PSV and NAVA did not reduce global lung injury compared with PCV but affected different biomarkers and attenuated diaphragmatic atrophy. NAVA increased the respiratory variability; however, NAVA yielded a similar SVA incidence as Noisy PSV. TRIAL REGISTRATION: This trial was registered and approved by the Landesdirektion Dresden, Germany (AZ 24-9168.11-1/2012-2). Abstract : Supplemental Digital Content is available in the text